New records of polychaetes (Annelida) for northern Ecuador - Trovant, Berenice; Elías, Rodolfo; Diez, María E.; De León González, Jesús Ángel (2012)
Even though Ecuador is one of the twelve mega-diverse countries in the world, the polychaetes are still poorly known. Twelve polychaete species, namely Hemipodia pustatula (Glyceridae); Microphthalmus arenarius (Hesionidae); Scoletoma zonata (Lumbrineridae); Nereis riisei, Pseudonereis gallapagensis (Nereididae); Armandia salvadoriana, Euzonus mucronata (Opheliidae); Phyllodoce multiseriata (Phyllodocidae); Pisione longispinulata (Pisionidae); Malacoceros indicus, Scolelepis (Scolelepis) acuta (Spionidae) and Opisthosyllis arboricola (Syllidae) are newly reported in the intertidal sandy beaches of Bunche (0839′ 01.98′′N 80803′ 55.01′′W) and Cabo San Francisco (0838′ 16.35′′N 80803′ 14.07′′W), Esmeraldas Province (Ecuador). Furthermore, an amended diagnosis of Pisione longispinulata is presented.